ISU TERORISME DAN RESPONS AKTIVIS MUDA ACEH - M. Hasbi Amiruddin (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2014)
This article wants to examine the extent of radical thought in the minds of the younger generation pervasive in Aceh. With the new Aceh conditions experienced several years of post-conflict situation safe again struck by discovered a number of terrorists who make Jalin mountains forest, Aceh Besar, as a military training ground. Also found are also a number of books that have a narrative that can bring inspiration radicalism and terrorism acts. The results of in-depth interviews of young activists in Aceh, can be explained that the concept of terrorism models struggle can not be accepted by young activists in the city of Banda Aceh. They have to understand the teachings of Islam that is relatively comprehensive and proportional. But their ideals in order to uphold Islamic shariah in Aceh is a necessity.